Influence of Ferronickel Slag on Impermeability of Seawater-Corroded Cement Soil Using an Electrochemical Test - Sanshan Chen; Feng Chen; Shenghao Tong (Advances in Civil Engineering, 2022)
Since the traditional penetration testing of cement soil is time-consuming, this paper introduces a new electrochemical testing method to study the effect of ferronickel slag powder on improving the impermeability of cement soil in the corrosive seawater environment. To this end, the mercury intrusion test was employed to analyze the change in the pore characteristics of cement soil, and the variation in the impermeability of cement soil was further explained from a microscopic point of view. The test results show that using the electrochemical method to test the impermeability of cement soil dramatically improves the efficiency of testing. The impermeability of cement soil gradually rises with an increase in its ferronickel slag powder content. Moreover, the optimal mass replacement ratio of the ferronickel slag powder and mineral powder composite to cement is 40% in the testing range of 0–40%. The mercury intrusion test results also confirm that the addition of ferronickel slag powder can decrease the most probable pore size and total porosity of cement soil; further, from a microscopic perspective, the ferronickel slag powder can help reduce the corrosion of cement soil by seawater. The above test conclusions are consistent with the results of the traditional permeability test. Our findings not only imply that ferronickel slag powder can lessen the effect of seawater on the corrosion of cement soil but prove that the electrochemical test is a reliable and straightforward method for determining the impermeability of cement soil.